Web conferencing and remote laboratories as part of blended learning in engineering and science: A paradigm shift in education or more of the same? - Mackay, S.; Fisher, Darrell (2011)
The purpose of this chapter is to provide an overview and subsequent application of research into the impact web conferencing and remote laboratories have on engineering and science education within the context of blended learning. The impact is examined especially in assessing the reaction and achievement of learners in using these new technologies compared to that of a traditional classroom or (the currently popular approach of) asynchronous e-learning. In recent years, there has been a significant increase in the level of remote or distance learning (or e-learning) using the Internet. One of the gaps in current research is the examination of the impact of web conferencing and remote science and engineering laboratories on the learning experience. The chapter is commenced by defining e-learning, synchronous, asynchronous and blended learning. Hereafter, web conferencing and remote laboratories are then defined and reviewed in detail. The impact that web conferencing and remote labs have on the e-learning experience as compared to the classroom and asynchronous approaches is then examined. The chapter is concluded by an examination of our research into what the perceived requirements are for web conferencing and remote laboratories and suggestions are given on how to apply web conferencing and remote labs to engineering and science education.